Carbohydrate supplementation after exercise affects mood state at high altitude - Kambis, K. W.; Fulco, C. S.; Friedlander, A. L.; McQuaid, D. B.; Jackson, C. W.; Ickes, S.; Muza, S. R.; Rock, P. B.; Cook, L.; Cymerman, A. (13. International Hypoxia-Symposium, February, 19-22, 2003, Banff, Alberta (Kanada), 2003)
At sea level, carbohydrate ingestion during prolonged strenuous exercise maintains blood glucose levels, improves performance and, enhances mood. The effect of carbohydrate supplementation on mood after prolonged exercise at high altitude has not been investigated. PURPOSE: To determine if carbohydrate supplementation during passive recovery from prolonged exhaustive exercise at 4300 m will alter mood state. METHODS: 16 healthy informed male subjects were divided into 2 groups matched for age (25.2 6 1.8 yr), weight (77.5 6 2.9 kg), and VO2max (51.0 6 2.36 mL/kg/min-1). In double-blind fashion, fasted subjects performed a maximum effort 720 KJ time trial on days 3 and 10 of residence at 4300 m. At the beginning of the time-trial and every 15 minutes thereafter, one group (FED) consumed a 10% carbohydrate solution (0.7 g/kg bw) while the other group (TREATMENT) consumed an indistinguishable placebo drink. Water was given ad lib during exercise. Work rate was self-adjusted. Prior to exercise and during recovery at 5 and 20 min post exercise, subjects completed the Feelings Profile (FP), a 19 item short form (Jackson, et al. 1991) of the Profile of Mood States. Within 20 min post exercise, TREATMENT subjects consumed a 10% carbohydrate (0.7 g/kg bw) drink while the FED group consumed the placebo. Fluid volumes were adjusted for exercise duration. RESULTS: For the TREATMENT group at 20 min of recovery, post-exercise carbohydrate supplementation decreased confusion on days 3 and 10, and increased fatigue on day 10. CONCLUSION: During recovery from exhaustive exercise at high altitude, post-exercise carbohydrate supplementation effectively reduces confusion but unexpectedly increases feelings of fatigue. These data may reflect a competition for blood flow between the brain and the carbohydratesuffused gut. Supported by: The Borgenicht Program, The Jeffress Memorial Trust, The Veterans Administration, and The U.S. Department of Defense.